English Translation of Sergio Ramírez’s “Abbott y Costello”: A Terminological Approach - Chaves Fernández, Lindsay (2021)
The current paper proposes an English translation of the short story “Abbott y Costello”, by the Nicaraguan Sergio Ramírez. To this end, a terminological approach was used in the selection, search in equivalent texts, and English translation of 50 complex terms, based on the recommendations in Sherry E. Gapper’s Manual de gestión terminológica. In addition, a translation-based analysis is presented for the selected terms, along with concluding remarks. Implications for theory and practice are also discussed and recommendations for literary translation are provided.